Free lunch - Ogle, Rex (W. W. Norton & Company, Inc., 2019)
"A distinctive new voice: Rex Ogle's story of starting middle school on the free lunch program is timely, heartbreaking, and true. Free Lunch is the story of Rex Ogle's first semester in sixth grade. Rex and his baby brother often went hungry, wore secondhand clothes, and were short of school supplies, and Rex was on his school's free lunch program. Grounded in the immediacy of physical hunger and the humiliation of having to announce it every day in the school lunch line, Rex's is a compelling story of a more profound hunger -- that of a child for his parents' love and care. Compulsively readable, beautifully crafted, and authentically told with the voice and point of view of a 6th-grade kid, Free Lunch is a remarkable debut by a gifted storyteller"--